FEATURES OF INDICATORS OF DAILY MONITORING OF ARTERIAL PRESSURE IN MEN WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE IN THE CONTEXT OF COMORBIDITY - Evgeny Vyacheslavovich Kozlov; Roman Anatolyevich Yaskevich; Olga Leonidovna Moskalenko; Ksenia Nikolaevna Kochergina (Siberian Journal of Life Sciences and Agriculture, 2019)
The purpose of the study. To study the features of indicators of daily monitoring of blood pressure in men with chronic obstructive pulmonary disease (COPD) in comorbidity. Materials and methods. 44 male patients with COPD in combination with arterial hypertension (AH) and 21 patients with COPD without AH were examined. The comparison group included 32 patients with hypertension without COPD. The study Protocol included: clinical, instrumental and laboratory methods. Results. Comparative analysis of the studied parameters of SMAD in the studied groups allowed us to identify the following features. Patients with COPD under comorbidity conditions showed higher average daily blood pressure (BP) and increased BP variability, which can be considered as a risk factor for an unfavorable prognosis of the disease. Established statistically significant differences in terms of the magnitude of the morning rise (OPS) and the speed of the morning rise (SUP). In patients with COPD under comorbid conditions, the pathological types of the daily non-dipper and night-picker blood pressure curve prevailed, characterized primarily by an insufficient degree of night-time blood pressure reduction. Conclusion. It was established that in patients with COPD in terms of comorbidity there are not only disturbances in the variability of blood pressure, but also more pronounced changes in the daily blood pressure profile in comparison with other groups.